2006
DOI: 10.1111/j.1365-2934.2006.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision revisited

Abstract: We make some suggestions for more complex versions that may be suitable as the profession develops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…There is diversity in thinking about clinical supervision as it encompasses various ideas, different approaches and methods (Jones 2006). It has been acknowledged that the term clinical supervision itself is problematic as it is interpreted differently by different groups depending on the origin/historical use of the word, dynamic changes, relevance of the concept to different cultural groups, the language spoken and the meaning attached to this language (Walsh et al 2003;Shanley & Stevenson 2006). Bogo and McKnight (2008) strongly recommend the use of consistent terms in regards to supervision in order to facilitate communication about this area.…”
Section: Introductionmentioning
confidence: 99%
“…There is diversity in thinking about clinical supervision as it encompasses various ideas, different approaches and methods (Jones 2006). It has been acknowledged that the term clinical supervision itself is problematic as it is interpreted differently by different groups depending on the origin/historical use of the word, dynamic changes, relevance of the concept to different cultural groups, the language spoken and the meaning attached to this language (Walsh et al 2003;Shanley & Stevenson 2006). Bogo and McKnight (2008) strongly recommend the use of consistent terms in regards to supervision in order to facilitate communication about this area.…”
Section: Introductionmentioning
confidence: 99%
“…They expect, however, that their support is reciprocated by all other stakeholders, not least the municipal executive team. The reform proposes rather specific guidelines of more direct and close, follow-up patient care, all of which demands greater resources (staff and budgetary) [11, 12]. Nurse leaders are acutely aware that their management responsibilities are very often different from those of other professions [29], due to the round-the-clock nature of health care service to patients whose lives are dependent on the nursing staff’s ability to see the patient’s every need and execute care accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…One informant in our study (a leader of a nursing home) was adamant that the nurse leader could benefit greatly from guidance/consultation in daily operations. These requests may not be unreasonable as other studies have shown that continuous guidance was needed in order for the organisation to attain the professional goals it set for itself [32, 12, 33, 34]. Health care regulators may need to consider possible ways to provide guidance and counseling, with telephony and other IT technologies certainly worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…In any CS event, a model can be beneficial in providing focus. Proctor's model (1986) highlights three areas or functions (Fig. ): normative/managerial, restorative/supportive and formative/educative.…”
Section: Clinical Supervisionmentioning
confidence: 99%